Staatliche Schuldenkrisen: Das Beispiel Griechenland - Heinz-Dieter Smeets (Research On Money in the Economy (ROME), 2010)
– This paper analyzes the Greek debt crisis. It is shown how the rescue package of 110 bn euro is shared among the IMF and the Euroarea-members in order to overcome the short-run problems. For the longer-run solution of the crisis several exit scenarios are presented and discussed: Under what conditions is the bail-out successful? Should Greece abandon the euro? Is a debt restructuring or default inevitable? In the end, the burden of adjustment has to be shared. Bondholders will lose some of their money by a haircut. Greek taxpayers will be paying higher taxes, retiring later, and taking cuts in public spending as do Euro-area taxpayers.
Keywords: H60; H62; H63; H68; E58; 330; Greek debt crisis; bail out; exit scenarios; debt restructuring